Diamonds are forever, computers are not : economic and strategic management in computing markets - Greenstein, Shane M. (Imperial College Press ; Distributed by World Scientific Pub., 2004)
This is a collection of 43 essays about the economics and managementof information technology markets. The first part of the book focuseson events, notable birth dates and longstanding trends. The unifyingtheme revolves around the role of human economic behavior in the faceof uncertainty and confusion. The contributors' intent is to explain, educate and entertain to go beyond the obvious.